Internationalization of board members and compliance with mandatory disclosure: Empirical study of IFRS 3 (business combinations) in Brazil - Fernandes, S. R. B.; Lourenço, I. C. (XVII Encuentro AECA, 2016)
The determinants tested in the mandatory disclosure are usually about business and cultural factors. However, the board members have a strong power of decision on the information disclosed, so it is natural that the characteristics of board members can influence the fulfillment of disclosure. This study analyses the level of compliance with IFRS 3 and examines whether it is influenced by the level of internationalization of board members. Our results indicate a moderate level of compliance, which is greater the greater the weight of foreign board members and the weight of board members with training abroad.